Implementation of Decision Support System for Integrated Coastal Zone Management of Sustainable Mariculture Development Industry in Indonesia - Surya Hermawan (Civil Engineering Dimension, 2016)
Indonesia has abundant and potential coastal resources for future development of mariculture industry activities. However, complex problem is found in the land and coastal zoneutilization, among others: coastal environment degradation, resources depletion, conflict and overlapping utilization of marine area. New perspective of Decision Support System (DSS) forintegrated coastal zone management (ICZM) can be used to solve this complexity with respect to the results of high resolution of hydrodynamic and wave numerical model, water quality, andICZM. The aim of this paper is to determine the suitable site for the implementation of sustainable future development of mariculture in Galang Island, Riau Province, Indonesia. Asuitability map of geographic information system based on ICZM is indicated by sixteen thematic maps. Implementations of the comprehensive ICZM of DSS criteria prove that GalangIsland has a bright potential of Grouper mariculture development industry by sustainable suitable area of about 12,940 hectares